A randomized-controlled trial of arginine infusion in severe sepsis on microcirculation and metabolism. Issue 6 (June 2020) - Luiking, Yvette C.; Poeze, Martijn; Deutz, Nicolaas E.
Summary: Background & aims: Sepsis is hypothesized as an arginine deficient state, with lack of nitric oxide (NO) for adequate microcirculation and local perfusion. This study aimed to investigate if prolonged (72-h) intravenous l -arginine administration in sepsis patients improves microcirculation. Secondly, effects on arginine and protein metabolism, and organ function were studied. Methods: Critically ill patients with a diagnosis of septic shock participated in a long-term (72 h) randomized double-blind placebo-controlled parallel-group study. l -arginine-HCl (1.2 μmol kg −1 min −1 ; n = 9) or l -alanine (isocaloric control: 2.4 μmol kg −1 min −1 ; n = 9) was continuously infused. Primary study outcome was microcirculation, assessed as gastric mucosal perfusion by gastric tonometry (Pr-a CO2 gap) and skin perfusion by Laser Doppler flowmetry. Secondary endpoints were whole body (WB) arginine and protein metabolism, organ function and clinical outcomes. We measured global hemodynamics continuously for safety monitoring. Statistical analyses were performed by mixed model for repeated measures with treatment by time interaction as estimate for between-group difference. Results: Pr-a CO2 increased only in the l -arginine group ( p = 0.006), without a significant between-group difference ( p = 0.17). We found no significant differences in skin perfusion parameters. l -arginine infusion resulted in a larger increase of plasma arginine and ornithine concentrations ( p < 0.01), WB (endogenous) arginine appearance ( p < 0.001), WB NO synthesis ( p = 0.027) and WB arginine to urea conversion ( p < 0.001) than infusion of l -alanine. We found no effect on global hemodynamics, and protein metabolism by l -arginine infusion. Organ function parameters were unaffected, except for a significant difference between groups in intra-abdominal pressure over time ( p = 0.029). Conclusions: Prolonged intravenous l -arginine administration does not improve local perfusion and organ function despite an increase in WB NO synthesis. Administration is safe with regard to global hemodynamics, but the observed increase in Pr-a CO2 and intra-abdominal pressure warrants careful application of l -arginine infusion and further research, especially in the early stage of septic shock.